Titrimetric and Spectrophotometric Assay of Oxcarbazepine in Pharmaceuticals Using N-Bromosuccinimide and Bromopyrogallol Red - Nagaraju Rajendraprasad; Kanakapura Basavaiah; Kanakapura B. Vinay (International Journal of Analytical Chemistry)
Titrimetric and spectrophotometric methods are described for the determination of oxcarbazepine (OXC) in bulk drug and in tablets. The methods use N-bromosuccinimide (NBS) and bromopyrogallol red (BPR) as reagents. In titrimetry (method A), an acidified solution of OXC is titrated directly with NBS using methyl orange as indicator. Spectrophotometry (method B) involves the addition of known excess of NBS to an acidified solution of OXC followed by the determination of the unreacted NBS by reacting with BPR and measuring the absorbance of the unreacted dye at 460 nm. Titrimetry allows the determination of 6–18 mg of OXC and follows a reaction stoichiometry of 1 : 1 (OXC : NBS), whereas spectrophotometry is applicable over the concentration range of 0.8–8.0 μg mL-1. Method B with a calculated molar absorptivity of 2.52×104 L mol-1 cm-1 is the most sensitive spectrophotometric method ever developed for OXC. The optical characteristics such as limits of detection (LOD), quantification (LOQ), and Sandell's sensitivity values are also reported for the spectrophotometric method. The accuracy and precision of the methods were studied on intraday and interday basis. The methods described could usefully be applied to routine quality control of tablets containing OXC. No interference was observed from common pharmaceutical adjuvants. Statistical comparison of the results with a reference method shows an excellent agreement and indicates no significant difference in accuracy and precision. The reliability of the methods was further ascertained by recovery studies in standard addition procedure.